(untitled) (Bangladesh Journal of Medical Science, 2026)
Mobile health (mHealth) services are revolutionizing healthcare in developing nations, yet adoption among young users remains low despite increasing digital access. This study integrates the Unified Theory of Acceptance and Use of Technology 2(UTAUT-2) and the Information Systems Success (ISS) Model to explore adoption drivers in Bangladesh, replacing ‘price value’ with ‘intrinsic value’ to better assess user motivation. Surveying university students and analyzing data via PLS-SEM, findings show performance expectancy, intrinsic value and ISS factors (information, system and service quality) significantly boost satisfaction. Surprisingly, effort expectancy had little impact, likely due to high digital literacy. User satisfaction strongly predicted continued mHealth use intention. The study offers both theoretical contributions to technology adoption literature and practical guidance for developers and policymakers to improve mHealth engagement among young users. BJMS, Vol. 25 No. 02 April’26 Page: 496-506